ISOLASI SENYAWA ANTIOKSIDAN DARI DAUN ALPUKAT (PERSEA AMERICANA MILL.) - Putri, Mega
Antioxidant is a substance that can neutralize free radicals to prevent some degenerative diseases and the process of aging. Nowadays, industries of foods, pharmaceuticals, and cosmetics are interested in finding new resources of natural antioxidants. Most natural antioxidants come from plants, for example avocado leaves. The aim of this research was to isolate an antioxidant substance from avocado leaves extract and to determine the chemical group of the isolate obtained. Crude drugs of avocado leaves were extracted using reflux method with increasing polarities of solvents (nhexane, ethyl acetate, and ethanol). The IC50 reduction of DPPH, total carotenoid content, total flavonoid content, and total phenolic content, in n-hexane extract, respectively were 787,98 µg/mL, 16,31 g BE/100 g, 9,60 g QE/100 g, and 2,65 g GAE/100 g. The IC50 reduction of DPPH, total flavonoid content, total phenolic content, and total carotenoid content, in ethyl acetate extract, respectively were 521,82 µg/mL, 10,34 g QE/100 g, 5,59 g GAE/100 g, and 2,79 g BE/100 g. The IC50 reduction of DPPH, total carotenoid content, total phenolic content, and total flavonoid content, in ethanol extract, respectively were 54,43 µg/mL, 3,35 g BE/100 g, 1,93 g GAE/100 g, and 0,84 g QE/100 g. The IC50 value of ethanol extract showed that ethanol extract had the highest antioxidant activity among all extracts. Therefore, ethanol extract was chosen to be continued to the fractionation step. Ethanol extract was dissolved in hot water and then filtered. The filtrate was fractionated using liquid-liquid extraction (LLE) with n-hexane and ethyl acetate solvents. Ethyl acetate fraction was subfractionated using preparative TLC and there were 2 bands. Subfraction 1 was purified using preparative TLC and then the purity was observed using single development TLC and 2 dimensional TLC. Isolate A was characterized using specific spray reagents and spectrophotometry UV-Vis (with shifting reagents). Based on characterization, isolate A is predicted to be a flavonoid substance group which is a flavonol that has UV absorbances with maximum wavelengths at 260 nm and 366 nm, where there were free OH- group on C3 and an OH- group on C7 in its structure.